Description of a new species of Africoseiulella Kreiter (Acari: Phytoseiidae) from Egypt - El-Banhawy, El-Sayed M.; Nasr, Abdelrady K.; Ramadan, Mahmoud M. (Zootaxa, 2025)
The genus Africoseiulella Kreiter was based on a single species, Africoseiulella flechtmanni Kreiter collected in Tunisia. The second species of this genus, A. sedishazlensisensis El-Banhawy, Nasr & Ramadan n.sp is described in this paper, based on adult females and a male collected in Sedi El-Shazli village, in the southern province of the Red Sea, Egypt. The new species is distinguished from A. flechtmanni mainly by leg chaetotaxy, an unusual pilus dentilis, the insertions of setae St3 and St4, and the presence of a spinelike structure on coxae III and Ⅳ of the male.